In-out charge exchange measurements and 3D modelling of diagnostic thermal neutrals to study edge poloidal impurity asymmetries. (1st April 2022) - Cruz-Zabala, D J; Viezzer, E; Plank, U; McDermott, R M; Cavedon, M; Fable, E; Dux, R; Cano-Megias, P; Pütterich, T; van Vuuren, A Jansen; Garcia-Munoz, M; Garcia Lopez, J; et al.
Abstract: A new method was developed to model the neutral population produced by the gas puff based charge exchange recombination spectroscopy systems at ASDEX Upgrade (AUG). With this method, the edge impurity density on the high field side (HFS) and low field side (LFS) can be obtained without the need to apply a neutral beam injection system. The neutral penetration needed for the calculation of the impurity density is obtained with a new gas puff module implemented in the FIDASIM code. The LFS impurity density profile evaluated with the new gas puff module matches the impurity density calculated with standard beam-based charge exchange diagnostics. Impurity temperature, rotation and density profiles at the HFS and LFS of an AUG H-mode discharge are presented. Edge impurity toroidal and poloidal flows show asymmetric structures. The impurity density asymmetries obtained with the new gas puff module are consistent with the observed flow structure.